Fluconazole versus Candida albicans: A Complex Relationship - Graybill, John R. (American Society for Microbiology, 1998)
A murine model of systemic candidiasis was used to assess the virulence of serial Candida albicans strains for which fluconazole MICs were increasing. Serial isolates from five patients with 17 episodes of oropharyngeal candidiasis were evaluated. The MICs for these isolates exhibited at least an eightfold progressive increase from susceptible (MIC < 8 μg/ml; range, 0.25 to 4 μg/ml) to resistant (MIC ≥ 16 μg/ml; range, 16 to ≥128 μg/ml). Virulence of the serial isolates from three of five patients showed a more than fivefold progressive decrease in the dose accounting for 50% mortality and was associated with development of fluconazole resistance. Low doses of fluconazole prolonged survival of mice infected with susceptible yeasts but failed to prolong survival following challenge with a resistant strain. In addition, a decreased burden of renal infection was noted in mice challenged with two of the three resistant strains. This was consistent with reduced virulence. Fluconazole did not further decrease the level of infection. In the isolates with a decrease in virulence, two exhibited overexpression of CDR, which encodes an ABC drug efflux pump. In contrast, serial isolates from the remaining two patients with the development of resistance did not demonstrate a change in virulence and fluconazole remained effective in prolonging survival, although significantly higher doses of fluconazole were required for efficacy. Resistant isolates from both of these patients exhibited overexpression of MDR. This study demonstrates that decreased virulence of serial C. albicans isolates is associated with increasing fluconazole MICs in some cases but not in others and shows that these low-virulence strains may not consistently cause infection.